The Influence of Education Level, Accounting Knowledge and Accounting Training on the Use of Accounting Information Moderated by Environmental Uncertainty of Small and Medium Enterprises in the Trenggalek Region - Krissantina Eferyn; Meme Rukmini; Duwi Riningsih; Rahmat Yusam Awaludin; Ninik Asmarani (Electronic Journal of Education, Social Economics and Technology, 2026)
Examining the effects of education level, accounting knowledge, and accounting training on the use of accounting information is the goal of this study. Additionally, it seeks to determine whether environmental uncertainty moderates these associations.  The study uses the Partial Least Squares (PLS) method of Structural Equation Modeling (SEM).  With a coefficient of 0.328 and a t-statistic of 2.749, which are both above the crucial value of 1.96, the findings of the hypothesis test show that only Accounting Knowledge has a statistically significant effect on the usage of accounting information.  Accounting training and educational attainment, however, do not appear to have a major impact.  Additionally, there is no moderating effect of environmental uncertainty on the associations among education level, accounting knowledge, and accounting training with regard to the use of accounting information.  According to these findings, improving accounting expertise helps encourage the use of accounting data in decision-making more than just boosting educational requirements or providing training that lacks meaningful content.  In order to improve the efficient use of accounting data, the study emphasizes how crucial it is that public sector enterprises give technical accounting skill development top priority.